Intra‐operative high‐resolution mapping of slow wave propagation in the human jejunum: Feasibility and initial results. Issue 7 (1st March 2018) - Angeli, T. R.; O'Grady, G.; Vather, R.; Bissett, I. P.; Cheng, L. K.
Abstract: Background: Bioelectrical slow waves are a coordinating mechanism of small intestine motility, but extracellular human studies have been restricted to a limited number of sparse electrode recordings. High‐resolution (HR) mapping has offered substantial insights into spatiotemporal intestinal slow wave dynamics, but has been limited to animal studies to date. This study aimed to translate intra‐operative HR mapping to define pacemaking and conduction profiles in the human small intestine. Methods: Immediately following laparotomy, flexible‐printed‐circuit arrays were applied around the serosa of the proximal jejunum (128‐256 electrodes; 4‐5.2 mm spacing; 28‐59 cm 2 ). Slow wave propagation patterns were mapped, and frequencies, amplitudes, downstroke widths, and velocities were calculated. Pacemaking and propagation patterns were defined. Key Results: Analysis comprised nine patients with mean recording duration of 7.6 ± 2.8 minutes. Slow waves occurred at a frequency of 9.8 ± 0.4 cpm, amplitude 0.3 ± 0.04 mV, downstroke width 0.5 ± 0.1 seconds, and with faster circumferential velocity than longitudinal (10.1 ± 0.8 vs 9.0 ± 0.7 mm/s; P = .001). Focal pacemakers were identified and mapped (n = 4; mean frequency 9.9 ± 0.2 cpm). Disordered slow wave propagation was observed, including wavefront collisions, conduction blocks, and breakout and entrainment of pacemakers. Conclusions & Inferences: This study introduces HR mapping of human intestinal slow waves, and provides first descriptions of intestinal pacemaker sites and velocity anisotropy. Future translation to other intestinal regions, disease states, and postsurgical dysmotility holds potential for improving the basic and clinical understanding of small intestine pathophysiology. Abstract : This study evaluated the feasibility of high‐resolution (HR) slow wave mapping in the human small intestine, including defining spatiotemporal propagation patterns. Slow wave frequency, amplitude, downstroke width, and anisotropic velocity profile were quantitatively defined, and focal pacemakers and disordered propagation events were mapped. This study presents the first account of human HR intestinal mapping, offering a technique for quantitative assessment of intestinal bioelectrical activity and enabling future investigation of potential slow wave abnormalities in human diseases and/or postsurgical dysmotility.